Length-weight relationships and relative condition factor in razor surgeonfish, Prionurus laticlavius (Teleostei: Acanthuridae) from the southwestern coast of the Gulf of California, Mexico - Aguilar-Santana, Fernando; Trujillo-Millán, Oscar; Hernández-Olalde, Liliana; Schmitter-Soto, Juan J.; Castillo-Navarro, Harold; Arellano-Martínez, Marcial (Revista de Biología Marina y Oceanografía, 2022)
The razor surgeonfish, Prionurus laticlavius, listed on the IUCN Red List of Threatened Species under the Least Concern category, plays an important ecological role as energy regulator in reef communities, but it is sought by the aquarium and aquaculture industry, and also is consumed by people. This study estimated the length-weight relationship (LWR) and relative condition factor (Krel) in P. laticlavius. The equation for length-weight relationship was TW= 0.02 TL3.01 for the Overall category, and the relative condition factor was 1.28. A total of 379 fish (3-45.6 cm total length) were collected in the southwestern coast of the Gulf of California using harpoon (for large fishes) and hand net (for small fishes), of which 181 were females (20.2-45.6 cm), 137 males (20.6-43.4 cm), and 61 juveniles (3-19.5 cm). Allometric coefficient b of LWR for the Overall category suggested isometric growth (b = 3.01), positive allometric growth for juveniles (b = 3.14), and negative allometric growth for adults (2.75). Results of Krel showed higher values for females during the warm season. The population showed a good nutritional condition, mainly in the warm season. This work is the first to estimate LWR and Krel for P. laticlavius, which will inform stock assessment and the management of this species in the Gulf of California.